From missions to mainstream Franciscan efforts in Nueva Caceres, Kabikolan, 1578-1768 - Totanes, Stephen Henry S. (2006)
Soon after the Augustinian friars begin their evangelical work in 1565 and the 1570s in the islands of Cebu, Panay and Luzon, includig the Ilocos region in the north, a second group of Spanish missionaries, the Franciscans, began sustained evangelical work in southern Luzon and in the region known initially as Ibalon, and later, as Kabikolan. The Spanish Franciscan missionary efforts in the Philippine Islands continued until 1898 when they were forced to surrender jurisdiction over their parishes with the end of Spanish rule and the beginning of American occupation. For almost two centuries, the Franciscans organized native communities into towns to facilitate Christianization. By 1768, the Franciscan mission in Nueva Cáceres expanded to Eastern Visayas, among the inhabitants of the island of Samar. This paper analyzes these efforts in the context of similar Franciscan efforts in the southwestern portions of present-day United States, in the states of California, Texas, New Mexico, and Arizona.
Includes bibliographical references (pages 122-127).